(untitled) (Chichester, England, 2007)
Personal Content Experience is a comprehensive introduction to mobile personal content. The book introduces and explores issues such as context capture, user interfaces for continuous mobile use, UI design for mobile media applications, metadata magic, virtual communities, and ontologies. User interactions and behavioural patterns with personal content are also covered, resulting in a ‘GEMS’ lifecycle model for analysing media devices, services, applications, and user interfaces. In addition, the book describes an extensible software architecture targeted at content management in mobile devices, pointing out the essential topics that will benefit anyone developing mobile content-intensive applications and services.
Keywords: Cell phone systems,Hệ thống điện thoại di động